Association of serum alkaline phosphatase and depression in US adults: a population-based cross-sectional study - Liang, Yujiang; Mao, Yafei; Liang, Weizhong; Liang, Liping; Suo, Min; Xue, Juan; Yang, Hui (Frontiers in Psychiatry, 2023)
Background Depression, a serious public health disorder, is increasingly prevalent worldwide. An association between alkaline phosphatase (ALP) and neurological disorders has been reported. However, data on ALP and depression risk are scarce, which warrants attention. Methods We assessed the association between ALP and risk of depression in adults from the 2007–2014 National Health and Nutrition Examination Survey (NHANES). Depression was assessed using the Patient Health Questionnaire-9. Univariate and multivariate logistic regression were used to assess the association between ALP and risk of depression, and subgroup analyses were also performed. Results A total of 17,485 participants were included. The prevalence of depression was 9.3% (1,631/17,485) and ALP was significantly associated with the risk of depression when ALP was a categorical variable (quadratic or categorized by 79 U/L) in a multivariate logistic regression model after adjusting for confounding factors (≥79 U/L vs. <79 U/L, adjusted OR, 1.15; 95%CI, 1.02–1.29). Each 1-unit increase in ALP (log2) was associated with a 20% increase in depression prevalence (adjusted OR, 1.20; 95%CI, 1.06–1.36) when ALP was used as a continuous variable. Subgroup analysis showed that ALP was positively associated with the risk of depression with different characteristics. Conclusion Our findings suggest that higher alkaline phosphatase levels, even within the normal range, are significantly associated with a higher risk of depression in US adults. Such findings require further prospective studies to provide more evidence.